Kalkulator Berkarakter Berbasis Android terhadap Kemampuan Pemahaman Konsep pada Materi Barisan dan Deret Aritmatika Siswa Sekolah Menengah Atas - Nicolaos Crisfigo Putra; Hartono Hartono; Utin Desy Susiaty (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This research aims to determine how to produce an Android-based character calculator application on the ability to understand concepts in arithmetic sequences and series material for high school students that reaches the level of validity, practicality and. The method used in this research is the Research & Development method with the Borg and Gall model research design which consists of 7 stages, namely potential and problems, data collection, product design, design validation, design revision, product testing, and product revision. The subjects in this research were 31 students in class XI Science at SMA Negeri 9 Pontianak. This research uses indirect communication techniques and measurements with data collection tools in the form of validation sheets, questionnaires and test questions. The first research result, namely the validity, obtained from the material and media expert validation value of 89.77% with very valid criteria, the second, namely the practicality obtained from teacher and student questionnaires with a percentage of 96.64% with very valid criteria, while the practicality value was obtained from The posttest score is 83.87% of the KKM score of 76 so it is included in the very effective category. Thus, it can be concluded that the Android-based character calculator application media for the ability to understand concepts in arithmetic sequences and series material for high school students is classified as effective to use.